1997
DOI: 10.1074/jbc.272.42.26536
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Peptide-binding Domains of the Human V1a Vasopressin Receptor with a Photoactivatable Linear Peptide Antagonist

Abstract: The study of antagonist-binding domains of the human V1a vasopressin receptor was performed using a radioiodinated photoreactive peptide antagonist. This ligand displayed a high affinity for the receptor expressed in Chinese hamster ovary cell membranes, and specifically labeled two protein bands with apparent molecular mass at 85-90 and 46 kDa. Our results clearly show that the V1a receptor is degraded during incubation with the ligand and that the 46-kDa species is probably the result of the 85-90-kDa specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
91
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(97 citation statements)
references
References 46 publications
6
91
0
Order By: Relevance
“…14). At the present time, very few photoaffinity labeling studies have led to the direct determination of labeled amino acid residues in peptide G protein-coupled receptor; remarkable results with bovine V 2 receptor (15), human NK1 tachykinin receptor (16), and rat type A cholecystokinin receptor (17) allowed identification of covalently labeled residues with photoactivatable agonist analogues of AVP, substance P, and cholecystokinin, respectively.Very recently, a first radioiodinated photoreactive linear peptide antagonist has been used in our laboratory to photolabel the human and rat V 1a receptors (12,18,19). Our results have clearly indicated that covalent attachment of the [ 125 I]3N 3 Phpa-LVA occurs in a restricted domain of the human receptor including TMR VII.…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…14). At the present time, very few photoaffinity labeling studies have led to the direct determination of labeled amino acid residues in peptide G protein-coupled receptor; remarkable results with bovine V 2 receptor (15), human NK1 tachykinin receptor (16), and rat type A cholecystokinin receptor (17) allowed identification of covalently labeled residues with photoactivatable agonist analogues of AVP, substance P, and cholecystokinin, respectively.Very recently, a first radioiodinated photoreactive linear peptide antagonist has been used in our laboratory to photolabel the human and rat V 1a receptors (12,18,19). Our results have clearly indicated that covalent attachment of the [ 125 I]3N 3 Phpa-LVA occurs in a restricted domain of the human receptor including TMR VII.…”
mentioning
confidence: 59%
“…Very recently, a first radioiodinated photoreactive linear peptide antagonist has been used in our laboratory to photolabel the human and rat V 1a receptors (12,18,19). Our results have clearly indicated that covalent attachment of the [ 125 I]3N 3 Phpa-LVA occurs in a restricted domain of the human receptor including TMR VII.…”
mentioning
confidence: 59%
See 3 more Smart Citations